The role of Chest HRCT in diagnosis active tuberculosis & lung destruction - Soekardi, Adi; Icksan, Aziza Ghanie; Ernes, Audrina (Jurnal Prima Medika Sains, 2023)
Tuberculosis is a public health problem caused by Mycobacterium tuberculosis. In 2021 there will be 10.6 million cases in the world, and Indonesia ranks 2nd with 700,000 cases. In 2022, there will be 17,303 cases in North Sumatra Province and 2,430 cases in Medan City. In current practice, evaluation and diagnosis of active tuberculosis relies on bacteriological examination and Chest Radiographs. However, Chest Radiographs have limited specificity and high intraobserver and interobserver variability. HRCT is also not widely used as a routine option for patients suspected of suffering from tuberculosis, even though HRCT has high accuracy in detecting tuberculosis. We present a case of a patient with active pulmonary tuberculosis and lung destruction e.c. advanced pulmonary tuberculosis (MDR-Tuberculosis) (declared cured in 2018 after 2 years of treatment). This patient was evaluated with chest radiograph and chest HRCT. In this case, the initial findings on the Chest Radiograph, showed the impression of inactive tuberculosis but on further examination with chest HRCT, there was a tree in bud image which indicated active tuberculosis. This shows that there are limitations in diagnosing tuberculosis activity using Chest Radiographs. Due to the significant role of HRCT in the diagnosis of tuberculosis activity, it is necessary to consider the use of HRCT in the evaluation of patients with tuberculosis.